Financial Services to the Unbanked: the case of the Mzansi intervention in South Africa - Philip Kostov; Thankom Arun; Samuel Annim (Contemporary Economics, 2014)
The Mzansi intervention is a major initiative designed to provide banking services to the unbanked South African population. This study investigates the underlying variables that define the choice of a Mzansi account from a consumer perspective. Unlike previous studies, we do not assume that demand for financial services is a given but instead that it is underlain by perceptions and attitudes. Financial attitudes and perceptions are found to exert significant effects on financial choices. In particular, aspirations and forward-looking values are instrumental in facilitating access to finance.
Keywords: C52; D12; G29; 330; access to finance; variable selection; adaptive LASSO